Effect of Capital Adequacy Ratio, Return On Assets, Operating Costs On Operating Income, Loan To Deposits Ratio On Profit Growth (Case Study On Banking On The Indonesia Stock Exchange For The Period 2016-2019) - Fajar Putra, Adika; Arif Lubis, Muhammad; Simanjuntak, Saroha (Journal Of Management Analytical and Solution (JoMAS), 2021)
This research was conduted find out how the partial and simultan influence of financial performance that is Capital Adequacy Ratio (X1), Return On Assets (X2), Operational Expense to Operational Income Ratio (X3) and Loan to Deposits Ratio (X4) on the profit growth (Y). The research data used are banking company data for 2016-2019 and taken from idx.co.id. The population in this research amounted to 61 banking companies with a sample of 12 companies. This research was conducted from july 2020 to November 2020. This research used quantitative data that was processed with SPSS 25.0 with Multiple linear regression  analysis.  The  results  showed that  capital  adequacy ratio, loan to deposits ratio and Operational Expense to Operational Income Ratio had a significan effect on profit growth while the return on assets did not significantly influence to profit growth. Simultaneously, Capital Adequacy Ratio, Return On Assets, Operational Expense to Operational Income Ratio and Loan to Deposits Ratio and significantly influence to profit growth with a coefficient of 26,7% while the remaining 73.3% is influenced by other factors.